A method of quantitative evaluation of plant communities by their phytosociological spectra (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
We propose to make an ecological evaluation of plant communities based on their phytosociological spectra. Under the phytosociological spectrum we understand ratios of representation in the general species composition of a cenosis of species relating to different classes of the Braun-Blanquet system. We demonstrate that the first class of the phytosociological spectrum makes up from 22% to 45%. This indicates a transitional character of the flora of the studied plant communities. We propose to characterize such communities by similarity of their three first classes of the phytosociological spectra, rather than by characteristic species. We made ordination of the plant communities by phytosociological spectra, in which the axes represent classes according to Braun- Blanquet. We demonstrate that phytosociological spectra is changed along gradients of ecological factors. The ecological optima for some Braun-Blanquet classes were estimated using phytoindication data.
Keywords: phytosociological spectrum, vegetation classification, classes of Braun- Blanquet.